Searching for new young stars in the Northern hemisphere: the Pisces Moving Group - Binks, Alex S.; Jeffries, Robin D.; Ward, Jacob L. (Monthly notices of the Royal Astronomical Society, 2018)
Using the kinematically unbiased technique described in Binks, Jeffries & Maxted (2015), we present optical spectra for a further 122 rapidly rotating (rotation periods <6  d), X-ray active FGK stars, selected from the SuperWASP survey. We identify 17 new examples of young, probably single stars with ages of <200 Myr and provide additional evidence for a new Northern hemisphere kinematic association: the Pisces moving group (MG). The group consists of 14 lithium-rich G- and K-type stars that have a dispersion of only ∼3 km s−1 in each Galactic space velocity coordinate. The group members are approximately coeval in the colour-magnitude diagram, with an age of 30-50 Myr, and have similar, though not identical, kinematics to the Octans-Near MG.
Advance access publication 2017 September 9
Gesehen am 13.01.2021